An acute bout of static stretching: Effects on force and jumping performance - Power, K.; Behm, D.; Cahill, F.; Carroll, M.; Young, W. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION/PURPOSE: The objectives of this study were to examine whether a static stretching (SS) routine decreased isometric force, muscle activation, and jump power while improving range of motion (ROM). Second, the study attempted to compare the duration of the dependent variable changes with the duration of the change in ROM. METHODS: Twelve participants were tested pre- and post- (POST, 30, 60, 90, and 120 min) SS of the quadriceps and plantar flexors (PF) or a similar period of no stretch (control). Measurements during isometric contractions included maximal voluntary force (MVC), evoked contractile properties (peak twitch and tetanus), surface integrated electromyographic (iEMG) activity of the agonist and antagonistic muscle groups, and muscle inactivation as measured by the interpolated twitch technique (ITT). Vertical jump (VJ) measurements included unilateral concentric-only (no countermovement) jump height as well as drop jump height and contact time. ROM associated with seated hip flexion, prone hip extension, and plantar flexion-dorsiflexion was also recorded. RESULTS: After SS, there were significant overall 9.5% and 5.4% decrements in the torque or force of the quadriceps for MVC and ITT, respectively. Force remained significantly decreased for 120 min (10.4%), paralleling significant percentage increases (6%) in sit and reach ROM (120 min). After SS, there were no significant changes in jump performance or PF measures. CONCLUSION: The parallel duration of changes in ROM and quadriceps isometric force might suggest an association between stretch-induced changes in muscle compliance and isometric force output.